Use of specific mitochondrial complex inhibitors to investigate mitochondrial involvement on horse sperm motility and ROS production. (October 2022) - Giaretta, Elisa; Mislei, Beatrice; Martínez-Pastor, Felipe; Nesci, Salvatore; Spinaci, Marcella; Galeati, Giovanna; Nerozzi, Chiara; Mari, Gaetano; Tamanini, Carlo; Bucci, Diego
Abstract: Equine spermatozoa highly rely on oxidative phosphorylation for their energy management. The present work aimed to characterize the role of mitochondria on horse sperm motility and ROS production by incubating spermatozoa with specific inhibitors of the different mitochondrial complexes. Equine spermatozoa were incubated 1 h and 3 h at 37 °C with: complex I inhibitor rotenone (5 μM, ROT), complex II inhibitor dimethyl-malonate (10 mM, DMM), complex III inhibitor antimycin A (1.8 μM, ANTI), the uncoupling agent carbonyl cyanide m -chlorophenyl hydrazine (5 μM, CCCP), ATP synthase inhibitor oligomycin (5 μM, OLIGO), and 2 μL vehicle DMSO (control, CTL). Samples were analyzed for sperm motility and for mitochondrial membrane potential (MMP), mitochondrial integrity, mitochondrial O2 – production, and cytoplasmic H2 O2 . A multivariate analysis was performed on the data. CCCP caused a pronounced MMP reduction at both time points while ROT and ANTI showed the same effect at 3 h. All treatments at 3 h incubation significantly reduced the percentage of sperm with early changes in membrane permeability with active mitochondria. The H2 O2 production of live cells was low at 1 h incubation in all treatments; after 3 h a slight decrease in the percentage of low-H2 O2 producing cells was recorded. All treatments, except DMM, induced a significant decline in sperm motility and kinematics and modified the pattern of sperm subpopulations. The effect of DMM was evident only after 3 h, increasing the percentage of slow sperm subpopulation. In conclusion, the disruption of mitochondrial integrity induces an increase of mitochondrial ROS production that could be detrimental for cell function and survivior. Highlights: CCCP, Rotenone and Anitmycin inhibit mitochondrial function. CCCP, Rotenone and Anitmycin do not increase ROS production. After 3 h incubation stallion spermatozoa produce more H2 O2 than after 1 h incubation. Inhibition of mitochondrial function induces a decrease of motility parameters. Different mitochondrial inhibitors alter sperm motility subpopulations.